“TO BE HIS AQUILINE DOVE”: BIRD IMAGES IN M. TSVETAEVA’S BOOK OF POEMS “REMESLO” (Филологический класс, 2019)
The article considers the semantics and functions of bird images and ornithological motifs in M. Tsvetaeva’s book of poems “Remeslo” (Handicraft). The use of traditional symbols of folk poetry is traced, as well as the mechanism of creating the individual author’s tropes on their basis. Associations with various birds are typical of Tsvetaeva’s poetic approach and her self-identification. Therefore, the analysis of ornithological images allows us to clarify the notion concerning the features of the poetic world of the “Remeslo” and Tsvetaeva’s mytho-poetics. It is traced how the bird images in many respects form and connect the metaplot of different lyrical cycles and the book as a whole. The emphasis is put on the analysis of the cycles “Separation”, “Blessed news”, “Praise to Aphrodite”, and various poems thematically related to the parting with love, youth, and homeland. The poetic world of the “Remeslo” is densely populated by different birds: doves, eagles, skylarks, cranes, swallows, nightingales, swans, and falcons. They connect the earth and heaven, being the messengers of gods and mortals. The characters of the book and Tsvetaeva’s lyrical counterpart acquire bird’s virtues, exhibit various metamorphoses, turning into one or another bird. The emphasis is put on the device to contrast different birds in the lyrical plot, for example, a nightingale and a falcon in the poem “Our open spaces for Tatar arrows”, as well as to negative comparisons and rejecting the former bird’s “names”. It is concluded that the ornithological images are built into the oppositions significant for Tsvetaeva: “gods – humans”, “parting – meeting”, “homeland – foreign land”, and “youth – maturity”. The semantics of these images is mobile and changeable; it is revealed in the context of a poem, of a lyrical cycle, and sometimes of the entire creative work. The bird images contribute to the creation of Tsvetaeva’s autobiographical myth.